2020
DOI: 10.33448/rsd-v9i8.5078
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho agronômico do crescimento e coeficientes de produção do rabanete cultivado em diferentes tipos de cobertura morta

Abstract: A deposição de coberturas mortas em sistema plantio podem afetar diretamente componentes de vegetativos e coeficientes de produção de hortaliças. O rabanete por ser uma planta de pequeno porte e fácil produção e comercialização, detém poucas alternativas mais orgânicas de produção, com isso o presente trabalho buscou avaliar o crescimento e índices de coeficientes de produção do Raphanus sativus L. cultivado em diferentes tipos de cobertura morta vegetal. O trabalho foi desenvolvido ambiente protegido com tela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…The carnauba bagana is normally used as mulch and organic fertilizer for the carnauba trees themselves in Northeastern Brazil. Recent studies have demonstrated its viability in vegetable plantations (Souza et al, 2016;Gomes et al, 2020) and in the composition of substrates for the production of seedlings (Albano et al, 2017;Silva et al, 2017). The use of mulch has as one of the main benefits the reduction of water loss from the soil through evaporation, due to protection against direct insolation and reduction of soil temperature, important factors to promote plant development, especially in semi-arid regions such as the Brazilian Caatinga (Macêdo, 2007;Gomes et al, 2009;Silva et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The carnauba bagana is normally used as mulch and organic fertilizer for the carnauba trees themselves in Northeastern Brazil. Recent studies have demonstrated its viability in vegetable plantations (Souza et al, 2016;Gomes et al, 2020) and in the composition of substrates for the production of seedlings (Albano et al, 2017;Silva et al, 2017). The use of mulch has as one of the main benefits the reduction of water loss from the soil through evaporation, due to protection against direct insolation and reduction of soil temperature, important factors to promote plant development, especially in semi-arid regions such as the Brazilian Caatinga (Macêdo, 2007;Gomes et al, 2009;Silva et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Farmers in regions where carnaúba wax is produced commonly use this residue due to its low-cost and efficient ground-covering properties (Queiroga et al, 2002). Additionally, carnaúba bagana has also been successfully used as mulch in vegetable plantations (Souza et al, 2016;Gomes et al, 2020), and in the composition of substrates for seedlings production (Sousa et al, 2012;Souza et al, 2015;Araújo et al, 2017;Albano et al, 2017;Silva et al, 2017).…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…estudando a germinação de ervas espontâneas na Caatinga, encontraram resultados positivos de supressão total da germinação em solo solarizado. Maia Jr. et al (2020), trabalhando com a infestação de plantas daninhas em cultivos de feijão caupi, concluíram que a solarização utilizando coletor solar, associada a cobertura morta, inibe a infestação de plantas daninhas Gomes et al (2020). relata que o emprego de práticas agrícolas conservacionistas na produção de vegetal possibilita aos agricultores, principalmente o pequeno agricultor, alcançar um mercado de produtos diferenciados, com o aproveitamento de materiais disponíveis no local para a formação do agrossistema familiar.…”
unclassified